Assessment of quality of life in lung transplantation using a simple generic tool: Presented at the 19th Annual Meeting of the International Society of Heart and Lung Transplantation in San Francisco, April 1999. Issue 3 (1st March 2001) - Anyanwu, A C; McGuire, A; Rogers, C A; Murday, A J
Abstract : BACKGROUND: The EuroQol is a generic questionnaire developed to provide a simple method for assigning utility values to health. This study examines the applicability of the EuroQol to the measurement of quality of life in single, bilateral, and heart-lung transplantation. METHODS: A cross sectional study was performed in 87 patients awaiting lung transplantation and in 255 transplant recipients attending follow up clinics in four transplant units. RESULTS: In the waiting list group 61% reported extreme problems in at least one of the five EuroQol quality of life domains compared with 20% single lung recipients, 4% bilateral lung recipients, and 2% heart-lung recipients at 3 or more years after transplantation. The mean utility value of patients on the waiting list was 0.31. In comparison, utility values for recipients 3 years after transplantation were 0.61 for single, 0.82 for bilateral, and 0.87 for heart-lung transplants. The utility scores and health profiles of bilateral and heart-lung recipients were consistently superior to those of single lung recipients. Problems in all five domains were more frequent in single lung recipients. Subjective assessment with a visual analogue scale showed a similar trend. CONCLUSIONS: The EuroQol is a simple method of deriving a single utility value for quality of life and is responsive to changes after lung transplantation. It is worth considering as a means of monitoring quality of life after transplantation and as an index of quality of survival in research studies in solid organ transplantation. These data suggest that quality of life after transplantation of one lung is inferior to that after transplantation of two lungs.